Critical Synthesis Package: Family Conference OSCE - Shilpa Brown (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health sciences education for the Family Conference OSCE, and 2) a copy of the Family Conference OSCE instrument and supplementary files developed by Connie Schmitz, PhD and Jeffrey Chipman, MD. The Family Conference OSCE is an observed clinical assessment of communication and interpersonal skills of surgical residents in the discussion of end-of-life (EOL) issues and disclosure of complications (DOC). Communication and interpersonal skills are assessed by two family raters and two professional/clinical raters per resident per station using a 15-point communication skills checklist. The OCSE does require intense training of its family actor/raters, as well as investments in faculty time, cost of training, and staffing. However, ratings on this OSCE reveal high interitem reliability and good generalizability. This OSCE can serve in the assessment of the communication and interpersonal skills core competency, as mandated by the ACGME for all training programs. The Family Conference OSCE will allow residents to practice communicating difficult topics such as EOL and DOC to family members in a safe and structured environment prior to a real life situation.